Little Kids Rock and modern band in US schools: A punk problematic. Issue 1 (May 2023) - Smith, Gareth Dylan; Powell, Bryan; Knapp, David
The pervasive Eurocentric model of music education in the United States is hegemonic, pursuing a model of performance excellence in large ensembles that, by the time young people reach high school, excludes most from music making opportunities in school. Despite numerous efforts to challenge the dominant paradigm since the 1960s, little change has happened from within the music education profession. Since 2002, nonprofit organization Little Kids Rock (Music Will) has leveraged outsider perspectives and philanthropic resources to galvanize momentum nationally towards adoption of curricula and musicking practices that focus more on popular musics and lifelong learning. Through a programme of professional development, curriculum provision and instrument donations, Little Kids Rock has both engaged in active resistance against, and established strategic partnerships with, state governments, university departments, school districts, major industry players including the National Association of Music Merchants, and education brands such as Berklee College of Music. Little Kids Rock promotes a new stream of music making called "modern band" as a disruptive phenomenon that emphasizes creativity, cultural relevance and student-centred learning while reinforcing entrenched hegemonic structures. Drawing on the history of Little Kids Rock and the modern band movement, the authors use Kahn-Egan's (1998) five tenets of punk to frame a critical examination of the modern band phenomenon and the ways which Little Kids Rock operates at various points along punk's ideological spectrum in attempting to "transform lives through restoring, expanding and innovating music education" in US schools.